The impacts of combined social and economic empowerment training on intimate partner violence, depression, gender norms and livelihoods among women: an individually randomised controlled trial and qualitative study in Afghanistan. Issue 3 (16th March 2020) - Gibbs, Andrew; Corboz, Julienne; Chirwa, Esnat; Mann, Carron; Karim, Fazal; Shafiq, Mohammed; Mecagni, Anna; Maxwell-Jones, Charlotte; Noble, Eva; Jewkes, Rachel
Abstract : Introduction: We assessed whether the Women for Women International (WfWI) economic and social empowerment programme could reduce women's experiences of intimate partner violence (IPV) and depression in Afghanistan. Methods: We conducted a two-arm individually randomised controlled trial in six urban and peri-urban communities. Communities were selected by WfWI for being conflict affected and showing signs of economic vulnerability (eg, little or no education, living in extreme poverty). Individual eligibility were female, aged 18–49, able to consent to participate and one woman per household. At 22 months, three primary outcomes were assessed: past year physical IPV experience; past year severe IPV experience; depressive symptoms. There was no blinding to arms. We conducted an intention-to-treat analysis, controlling for age. We also conducted qualitative interviews at endline, analysed using thematic analysis. Results: 1461 women (n=933 married) were recruited and randomised. Retention at endline was n=1210 (82%). Primary outcomes were in the hypothesised direction, but showed no significant impacts: physical IPV (adjusted OR (aOR) 0.88 (0.62 to 1.23)), severe IPV (aOR 0.75 (0.50 to 1.11)) and depressive symptoms (β −0.35 (−1.19 to 0.48)). Women reported reduced food insecurity (β −0.48 (−0.85 to –0.12)), higher earnings (β 3.79 (0.96 to 6.61)) and savings (β 11.79 (9.95 to 13.64)). Women reported less gender-inequitable attitudes (β −0.89 (−1.15 to –0.62)), more household decision-making (β 0.35 (−0.04 to 0.74)) and increased mobility (aOR 1.78 (1.27 to 2.50)). Twenty-eight in-depth interviews were conducted. Conclusion: The intervention did not impact IPV or depression. The intervention did improve livelihoods, create more gender-equitable relationships and increase women's mobility. Translating these gains into IPV and depression reduction is critical. Trial registration number: NCT03236948, registered 2 August 2017.